SUMBER PENDANAAN, TEKNOLOGI INFORMASI, DAN KINERJA FINANSIAL PADA USAHA KECIL DAN MENENGAH PRA DAN SELAMA PANDEMI COVID-19 - Riskin Hidayat; Dian Anita Sari (FE Program Studi Manajemen, 2022)
This research test the mediating role of information technology on the influence of funding sources on the performance of SMEs before-during the COVID 19 pandemic. The sample of the study conducted is Coffee SMEs in Rembang Regency, which produces produces “Lelet Coffee”. In this study, all members of the population were sampled as 50 samples, but only 48 samples could be processed, because two samples were damage. The data analysis technique used path analysis with PLS. Test results show that funding sources had a significant positive impact on the performance of Lelet Coffee SMEs both pre-pandemic and during the Covid 19 pandemic. Similarly, when it is mediated through information technology, it can be seen that funding sources before and during the Covid 19 pandemic have a significant indirect impact on the performance of Coffee SMEs pre and during the covid-19 pandemic. In addition, the study shows that information technology has a significant positive impact on the performance of Coffee SMEs. This means that digital technology will play a very important role in driving the impact of funding sources on the financial performance of Rembang Regency's Coffee SMEs.Kata Kunci : funding sources, information technology, SME financial performance, covid-19 pandemic